Ceramic substrate, and semiconductor device substrate equipped therewith

JP7943922B2Active Publication Date: 2026-10-30NGK CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024572665
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-09-04
Filing Date
2024-03-06
Publication Date
2026-10-30
Estimated Expiration
2044-03-06

AI Technical Summary

Benefits of technology

【0015】 本発明によれば、セラミック基板に銅板が接合されている場合に、直流電圧を印加した際にその剥がれを抑制することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007943922000004
    Figure 0007943922000004
  • Figure 0007943922000005
    Figure 0007943922000005
  • Figure 0007943922000006
    Figure 0007943922000006
Patent Text Reader

Abstract

This ceramic substrate contains alumina, zirconia, yttria, and a glassy substance. The glassy substance includes Si, an alkali metal, and O as first components and one or more of Ca, Sr, and Ba as second components. The zirconia content is 5–14 wt%. When A is the value obtained by dividing the concentration in terms of oxides of the alkali metal that is a first component of the glassy substance by the total interfacial distance (grain boundary length) at which Al2O3, ZrO2, and SiO2 are adjacent to each other, B is the concentration in terms of oxides of the Si that is a first component of the glassy substance, and C is the total mass concentration in terms of oxides of the Ca, Sr, and Ba that are second components of the glassy substance, A / (B×C) is no more than 7.1×10-4.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a ceramic substrate and a substrate for a semiconductor device including the same.

Background Art

[0002] As a substrate for semiconductor devices used in power transistor modules and the like, a DBOC substrate (Direct Bonding of Copper Substrate) having a copper plate on the surface of a ceramic substrate is known (for example, Patent Documents 1 to 3).

Prior Art Literature

Patent Documents

[0003]

Patent Document 1

Patent Document 2

Patent Document 3

Summary of Invention

Problems to be Solved by the Invention

[0004] By the way, in the above-described substrate for semiconductor devices, the copper plate is bonded to the surface of the ceramic substrate, and the present inventors have found that when the oxygen ion conductivity of the ceramic substrate increases, the bonding strength between the ceramic substrate and the copper plate decreases when a DC voltage is applied, which may cause the copper plate to peel off.

[0005] The present invention has been made to solve the above problems, and an object of the present invention is to provide a ceramic substrate and a substrate for a semiconductor device that can suppress peeling of the bonded copper plate when a DC voltage is applied.

Means for Solving the Problems

[0006] Item 1. Alumina, and Zirconia and, Ittoria and, Glassy and, It contains, The glassy material is The first component contains Si, alkali metals, and O as elements. The second component includes at least one element selected from Ca, Sr, and Ba. The zirconia content is 5 to 14% by mass, Let A be the value obtained by dividing the concentration of the alkali metal, which is the first component of the glassy material, in terms of oxide, by the total distance (grain boundary length) between adjacent interfaces of Al2O3, ZrO2, and SiO2. Let B be the concentration of Si, the first component of the glassy material, in terms of oxide. When the total mass concentration of Ca, Sr, and Ba, which are the second components of the glassy material, is denoted as C in terms of oxides, The value of A / (B×C) is 7.1×10 -4 The following is a ceramic substrate.

[0007] Item 2. The ceramic substrate according to Item 1, wherein the mass ratio of the content of the alkali metal in terms of oxide to the content of the second glassy component in terms of oxide is 1.0 or less.

[0008] Item 3. The ceramic substrate according to item 1 or 2, wherein the zirconia content is 11% by mass or more.

[0009] Item 4. A ceramic substrate according to any one of items 1 to 3, wherein the mole fraction of yttria relative to zirconia is 0.015 to 0.035.

[0010] Item 5. A ceramic substrate according to any one of items 1 to 4, wherein the mass ratio of the total content of zirconia and yttria to the alumina content is 0.10 or more.

[0011] Item 6. The ceramic substrate according to any one of Items 1 to 5, wherein a mass ratio of the total content of the silica, magnesia, and the second vitreous component to the content of the alkali metal in terms of oxide is 25.0 or more.

[0012] Item 7. The ceramic substrate according to any one of Items 1 to 6, having a flexural strength of 550 MPa or more.

[0013] Item 8. The ceramic substrate according to any one of Items 1 to 6, having a flexural strength of 700 MPa or more.

[0014] Item 9. A substrate for a semiconductor device for mounting an electronic component, comprising the ceramic substrate according to any one of Items 1 to 8, and a copper plate bonded to the ceramic substrate, the substrate for a semiconductor device. Effects of the Invention

[0015] According to the present invention, when a copper plate is bonded to a ceramic substrate, peeling thereof can be suppressed when a DC voltage is applied. Brief Description of the Drawings

[0016] [Figure 1] It is a cross-sectional view showing one embodiment of a semiconductor device having a substrate for a semiconductor device according to the present invention. [Figure 2] It is a diagram showing a Boundary Map of Al2O3, ZrO2, and SiO2 and grain boundary lengths of the cross section of the ceramic substrate of Example 1 according to the present invention. [Figure 3] It is a cross-sectional SEM image of the ceramic substrate of Example 1 according to the present invention. [Figure 4] It is a cross-sectional SEM image of the ceramic substrate of Comparative Example 3 according to the present invention. [Figure 5] It is a diagram showing the relationship between impedance and frequency in the ceramic substrates of Example 1 and Comparative Example 3 according to the present invention. Modes for Carrying Out the Invention

[0017] Hereinafter, an embodiment of the ceramic substrate and the semiconductor device substrate using the same according to the present invention will be described with reference to the drawings. Figure 1 is a cross-sectional view of a semiconductor device having the semiconductor device substrate according to this embodiment.

[0018] <1. Overview of Semiconductor Devices> The semiconductor device according to this embodiment can be used as a power module in various electronic devices such as personal computers, large white goods, railways, electric vehicles, power generation (wind power generation, solar power generation, fuel cells, etc.), air conditioners, industrial robots, commercial elevators, household microwave ovens, induction rice cookers, and UPS (uninterruptible power supply).

[0019] As shown in Figure 1, the semiconductor device 1 according to this embodiment comprises a semiconductor device substrate 2, a first bonding material 5, a second bonding material 5', a semiconductor chip 6, bonding wires 7, and a heat sink 8.

[0020] The semiconductor device substrate 2 is a so-called DBOC substrate (Direct Bonding of Copper Substrate), comprising a plate-shaped ceramic substrate 3 which is an insulator, a first copper plate 4 bonded to one side (top surface) of the ceramic substrate 3, and a second copper plate 4' bonded to the other side (bottom surface). Details of the ceramic substrate 3 will be described later.

[0021] A transmission circuit is formed on the first copper plate 4. On the other hand, the second copper plate 4' is formed in a flat plate shape.

[0022] A semiconductor chip 6 is bonded to the upper surface of the semiconductor device substrate 2, specifically a portion of the upper surface of the first copper plate 4, via a first bonding material 5. Furthermore, the semiconductor chip 6 and the first copper plate 4 are connected by bonding wires 7.

[0023] On the other hand, a heat sink 8 is bonded to the lower surface of the semiconductor device substrate 2, that is, the lower surface of the second copper plate 4', via a second bonding material 5'. The heat sink 8 is a known type and can be made of a metal such as copper.

[0024] <2. Ceramic Substrate Configuration> Next, the ceramic substrate 3 will be described in detail. The ceramic substrate 3 contains alumina (Al2O3), zirconia (ZrO2), yttria (Y2O3), glassy material, and the remainder. The glassy material also contains a first component and a second component. The first component contains Si, alkali metals, and O as elements, and the second component contains at least one element selected from Ca, Sr, and Ba as elements. However, the glassy material may contain other components. The content of the constituent elements of this ceramic substrate 3 will be described below.

[0025] The alumina content is preferably, for example, 75% by mass or more and 90% by mass or less, and more preferably 85% by mass or more and 90% by mass or less.

[0026] The zirconia content is preferably, for example, 5% by mass or more and 14% by mass or less, and more preferably 11% by mass or more and 14% by mass or less. A zirconia content of 5% by mass or more improves the strength of the ceramic substrate 3. Furthermore, it is believed that this can suppress the ceramic substrate 3 from having an excessively low linear thermal expansion coefficient, thereby reducing the difference in linear thermal expansion coefficients between the ceramic substrate 3 and the first and second copper plates 4, 4'. As a result, the thermal stress generated at the bonding interface with the copper plate 4 can be reduced, contributing to the suppression of crack formation in the ceramic substrate 3 at the bonding interface. Additionally, if the zirconia content is 11% by mass or more, the flexural strength of the ceramic substrate 3 can be increased (for example, as shown in Examples 3 and 6 described later, the flexural strength can be 700 MPa or more).

[0027] On the other hand, by limiting the zirconia content to 14% by mass or less, it is possible to suppress excessive reactions at the bonding interface during copper plate bonding, thereby suppressing the formation of voids at the bonding interface. This is because alumina and zirconia have different wettability with the Cu-O eutectic liquid phase during copper plate bonding. Furthermore, by limiting the zirconia content to 14% by mass or less, the impedance of the ceramic substrate 3 can be improved without increasing the silica content, as will be described later.

[0028] The yttria content is preferably 0.3% by mass or more and 2.0% by mass or less, and more preferably 0.5% by mass or more and 1.2% by mass or less. By setting the content to 0.3% by mass or more, it is thought that the proportion of the monoclinic phase in the zirconia crystal phase will be suppressed, while the proportion of the tetragonal phase will be increased. As a result, the mechanical strength of the ceramic substrate 3 can be improved and it is thought that this will contribute to suppressing the occurrence of cracks in the ceramic substrate 3 at the bonding interface.

[0029] On the other hand, by limiting the yttria content to 2.0 mass% or less, it is thought that the proportion of cubic crystals in the zirconia crystal phase can be suppressed, while the proportion of tetragonal crystals can be increased. As a result, the mechanical strength of the ceramic substrate 3 can be improved, and this is thought to contribute to suppressing the occurrence of cracks in the ceramic substrate 3 at the bonding interface.

[0030] By setting the mole fraction of yttria content to zirconia content within the range of 0.015 to 0.035, yttria-stabilized zirconia (YSZ) is formed, exhibiting volume increase behavior at the tips of microcracks due to martensitic transformation. In YSZ, yttria is solid-dissolved in zirconia. As a result, resistance to crack propagation is increased, and fracture toughness and mechanical strength can be effectively improved.

[0031] Therefore, in the ceramic substrate 3 of this embodiment, zirconia and yttria exist as yttria-stabilized zirconia, but they may also exist individually. However, in this invention, these two embodiments will be described as equivalent. Therefore, even when zirconia and yttria are described individually, they may exist in the ceramic substrate 3 as yttria-stabilized zirconia.

[0032] Furthermore, it is preferable that the mass ratio of the total content of zirconia and yttria to the alumina content be 0.10 or higher. This is because a mass ratio of 0.10 or higher can improve the flexural strength. On the other hand, it is preferable that this mass ratio be 0.30 or lower. This is because, since the thermal conductivity of zirconia is lower than that of alumina, if this mass ratio exceeds 0.30, it may not be possible to maintain sufficient thermal conductivity as an insulating heat dissipation circuit board.

[0033] Furthermore, the presence of alumina, zirconia, and yttria as oxides themselves in the ceramic substrate 3 can be proven by XRD, etc.

[0034] Next, we will explain glassy materials. As described above, glassy materials contain a first component containing Si, alkali metals, and O as elements, and a second component containing at least one element selected from Ca, Sr, and Ba as elements. However, these elements mainly exist as oxides such as silica (SiO2), alkali metal oxides, calcium oxide (CaO), strontium oxide (SrO), and barium oxide (BaO), so examples of these will be explained below. Note that the first component may also contain Mg, which exists as an oxide such as magnesia (MgO) in glassy materials.

[0035] First, let's explain the first component. The silica content is preferably between 0.1% by mass and 2.5% by mass. When the silica content is 0.1% by mass or more, the oxygen ion conductivity of the ceramic substrate 3 is suppressed, as will be described later, and the impedance can be improved. On the other hand, if the silica content is too high, the strength of the ceramic substrate 3 may decrease, so to suppress this, the silica content is preferably 2.5% by mass or less.

[0036] The magnesia content is preferably 0.05% by mass or more and 0.5% by mass or less, and more preferably 0.10% by mass or more and 0.3% by mass or less. By setting the magnesia content to 0.05% by mass or more, it is thought that the ceramic substrate 3 can be sintered without excessively high firing temperatures, and the coarsening of alumina particles and zirconia particles can be suppressed. As a result, the mechanical strength of the ceramic substrate 3 can be improved, and it is thought that this contributes to suppressing the occurrence of cracks in the ceramic substrate 3 at the bonding interface with the copper plate 4. In addition, it is thought that a sufficient amount of MgAl2O4 crystals (hereinafter referred to as "spinel crystals") can be generated in the ceramic substrate 3, and the wettability with the Cu-O eutectic liquid phase during copper plate bonding can be improved. As a result, it is thought that this contributes to suppressing the occurrence of voids at the bonding interface.

[0037] On the other hand, by limiting the magnesia content to 0.5 mass% or less, it is possible to suppress the excessive formation of spinel crystals with low mechanical strength, thereby improving the mechanical strength of the ceramic substrate 3. As a result, this is expected to contribute to suppressing the occurrence of cracks in the ceramic substrate 3 at the bonding interface.

[0038] Alkali metal ions have the function of breaking the Si-O bonds of SiO₂ to form Non Bridging Oxygen (NBO), and the NBO serves as ion diffusion sites to generate oxygen ion conductivity. Examples of such alkali metals include sodium, potassium, lithium and the like, and two or more of these may be contained. These are present in the ceramic substrate 3 in the form of sodium oxide (Na₂O), potassium oxide (K₂O), and lithium oxide (Li₂O). Any of these alkali metal oxides may be used ,rear as shown in the examples described Become like an object , which the present inventor has confirmed.

[0039] Each of the second components is a vitreous network-modifying oxide, which is incorporated into the skeleton of the vitreous network-forming oxide mainly composed of silica (SiO₂), and exhibits the function of changing the chemical and physical properties of the vitreous material. In particular, when calcium oxide (CaO), strontium oxide (SrO), and barium oxide (BaO) are contained in the vitreous material containing the alkali metal oxide as described above, ion conduction with NBO as diffusion sites is suppressed, which is known to reduce electrical conductivity. In addition, the function of reducing electrical conductivity increases in the order of CaO < SrO < BaO.

[0040] This reason is based on that the larger the difference in radius between monovalent alkali metal ions and divalent ions, the greater the blocking effect of the divalent ions that inhibits the movement of alkali metal ions, and that the polarizability to non-bridging oxygen ions decreases, the bond between adjacent alkali metal ions and oxygen ions becomes stronger, and the mobility of alkali metal ions decreases.

[0041] Furthermore, based on this reason, the insulating properties can be further enhanced by including CaO, SrO, and BaO in the alkali metal oxide-containing glass. Therefore, it is possible to improve the property that the present invention solves, in which, when a DC voltage is applied, oxygen ions conduct from the negative electrode side to the positive electrode side inside the ceramic substrate, reducing the bonding strength between the electrode and the ceramic substrate.

[0042] Furthermore, the second component of the glass only needs to contain one or more of the following: CaO, SrO, and BaO.

[0043] In this ceramic substrate, the mass ratio of alkali metal oxide content to the content of the second component in terms of glassy oxide content is preferably 1.0 or less. This effectively suppresses oxygen ion conduction. As a result, it is possible to suppress a significant decrease in the bonding strength between the ceramic substrate 3 and the copper plate after applying a DC voltage.

[0044] Furthermore, the mass ratio of the total content of silica, magnesia, and glassy second component to the alkali metal oxide content is preferably 25.0 or higher, and more preferably 30.0 or higher. This allows for even more effective suppression of oxygen ion conduction. In particular, it has been found that when this value is less than 25.0, the bonding strength between the ceramic substrate 3 and the copper plates 4,4' decreases significantly as the value decreases after applying a DC voltage. The upper limit of this value can be, for example, 65.0 or lower.

[0045] Furthermore, since sodium affects electrical conductivity, it is preferable that the sodium content in the ceramic substrate 3, in terms of oxide, be 0% by mass or greater than 0% by mass and 0.05% by mass or less.

[0046] Furthermore, the content of glassy oxides in the ceramic substrate 3 can be, for example, 0.9% to 3% by mass. This is because if it is less than 0.9% by mass, oxygen ion conduction cannot be sufficiently suppressed, while if it exceeds 3% by mass, sufficient flexural strength cannot be obtained.

[0047] The content of the remaining material is preferably 0.5% by mass or less, and more preferably 0.05% by mass or less, in terms of oxides. This is thought to suppress excessive sintering of the ceramic substrate 3 even when the firing temperature is not excessively high, and to reduce the porosity of the ceramic substrate 3. As a result, the mechanical strength of the ceramic substrate 3 can be improved, and this is thought to contribute to suppressing the occurrence of cracks in the ceramic substrate 3 at the bonding interface with the copper plate 4.

[0048] In this embodiment, the content of the constituent elements of the ceramic substrate 3 is calculated in terms of oxides as described above. However, the constituent elements of the ceramic substrate 3 may or may not exist in the form of oxides. For example, at least one of Y, Mg, and Ca may not exist in the form of oxides but be dissolved in ZrO2. Similarly, some alkali metals may not exist in the form of oxides. Even for alkali metals that do not exist in the form of oxides, the content is calculated in terms of oxides.

[0049] The oxide content of the constituent elements of the ceramic substrate 3 is calculated as follows: First, the constituent elements of the ceramic substrate 3 are qualitatively analyzed using an X-ray fluorescence analyzer (XRF) or an energy-dispersive analyzer (EDS) attached to a scanning electron microscope (SEM). Next, each element detected by this qualitative analysis is quantitatively analyzed using an ICP emission spectrometer. Then, the content of each element measured by this quantitative analysis is converted to oxide.

[0050] The elements in the remainder may be those that are intentionally added or those that are inevitably mixed in. There are no particular restrictions on the elements in the remainder, but examples include Fe (iron), Ti (titanium), and Mn (manganese).

[0051] Furthermore, the glassy material described above cannot exist within the matrix grains, but rather at the grain boundaries, which are regions surrounded by the matrix grains. There are three types of grain boundaries, for example, Al2O3 / Al2O3, Al2O3 / YSZ, and YSZ / YSZ. From a macroscopic perspective, there are two types of grain boundaries: those within the ceramic substrate 3 that are not exposed to the outside (the three types mentioned above), and those on the surface that are exposed to the outside. In addition, trace amounts of glassy components may dissolve in Al2O3 and YSZ.

[0052] Furthermore, the inventors obtained the following findings regarding the grain boundaries of glassy materials. Specifically, the findings regarding the grain boundaries of glassy materials were quantified and evaluated as follows. First, the following A to C were defined. A: The alkali metal density at the grain boundaries was simulated and defined as A by calculating the mass concentration ratio (mass % / μm) of alkali metals in terms of oxides relative to the total interfacial distance (grain boundary length) between adjacent Al2O3, ZrO2, and SiO2 atoms. The method for measuring grain boundary length will be described later. B: Let B be the mass concentration (mass%) of SiO2. By calculating the ratio of A to B (A / B), the effect of alkali metals in forming NBOs on the electrical insulation properties of silica was simulated. It is thought that a higher A / B value tends to indicate increased oxygen ion conductivity. C: C represents the total mass concentration (mass%) of Ca, Sr, and Ba in terms of oxides, which suppress the formation of NBO by alkali metals. The difficulty in generating NBO was simulated by calculating the ratio of A / B to C (1 / μm·mass%) in A / B / C (=A / (B×C)). Furthermore, A / (B×C) can also be defined as (mass concentration of alkali metals in terms of oxides / total mass concentration of Ca·Ba·Sr in terms of oxides) / (SiO2 mass concentration × total interfacial distance).

[0053] The above calculated value (A / (B×C)) changes depending on the mixing ratio of the constituents, the diameter of the raw material powder, the firing time and temperature, etc., but the inventors have determined it to be 7.1×10 -4 We found that within the following range, DC durability improves and the joint strength ratio is also excellent. Furthermore, the inventors found that the lower this calculated value, the higher the flexural strength. From the viewpoint of improving flexural strength, this calculated value is 2.0 × 10 -4 It is even more preferable that the following conditions apply: 1.5 × 10 -4 The following were found to be particularly preferable.

[0054] <3. Method for manufacturing ceramic substrates and semiconductor device substrates> Next, a method for manufacturing ceramic substrates and semiconductor device substrates will be described. First, the powder materials of the constituent elements mentioned above are crushed and mixed, for example, using a ball mill.

[0055] Next, an organic binder (e.g., polyvinyl butyral), a solvent (xylene, toluene, etc.), and a plasticizer (dioctyl phthalate, etc.) are added to the pulverized and mixed powder material to form a slurry-like substance.

[0056] Subsequently, the slurry-like substance is molded into the desired shape using a desired molding method (e.g., die press, cold isohydrostatic press, injection molding, doctor blade method, extrusion molding method, etc.) to produce a ceramic molded body.

[0057] Then, the ceramic molded body is fired in an oxygen or air atmosphere to complete the ceramic substrate. In this case, the maximum temperature is preferably 1450 to 1650°C, and more preferably 1555 to 1565°C. The holding time at the maximum temperature is preferably 0.7 to 1.0 hours, and more preferably 0.8 to 0.9 hours. The heating rate from 1,000°C to the maximum temperature is preferably 5 to 15°C / min, preferably 8 to 12°C / min, and particularly preferably 9 to 11°C / min. The heating time from the start to the maximum temperature is preferably 3 to 20 hours, and more preferably 5 to 15 hours.

[0058] It has been empirically observed that when the heating rate is increased relative to the above settings, the proportion of voids within the ceramic substrate increases proportionally, leading to a reduction in mechanical strength. Furthermore, since the above maximum temperature is in a temperature range exceeding the melting point of typical glass, as the time spent above the glass melting point, including the heating process and the maximum temperature, increases, grain growth in the matrix base material is promoted, and the network of glass particles present in a mesh-like structure at the grain boundaries tends to break down, resulting in a more scattered behavior. This weakens the electrical insulation effect. Therefore, it is preferable to shorten the heating time by increasing the heating rate as described above, and also shorten the holding time at the maximum temperature. Based on this mechanism, the above firing conditions were optimized.

[0059] Next, a method for manufacturing a semiconductor device substrate will be described. First, a laminate is formed by placing copper plates 4 and 4' with oxidized surfaces on the upper and lower surfaces of a ceramic substrate 3, and heating it for about 5 to 20 minutes (for example, about 10 minutes) under a nitrogen atmosphere at 1065°C to 1083°C. Due to the heating, a Cu-O eutectic liquid phase is formed at the interface where the ceramic substrate 3 and the copper plates 4 and 4' are joined. The thickness of each copper plate 4 and 4' can be, for example, 0.1 to 2.0 mm.

[0060] Next, the Cu-O eutectic liquid phase solidifies by cooling this laminate, and the copper plates 4 and 4' are bonded to the ceramic substrate 3. In this way, the semiconductor device substrate 2 is completed. The transmission circuit formed on the copper plate 4 on the surface to which the semiconductor chip 6 is bonded can be formed, for example, by the subtractive method or the additive method. [Examples]

[0061] The following describes embodiments of the present invention. However, the present invention is not limited to the following embodiments.

[0062] <1. Fabrication of ceramic substrates> Ceramic substrates for Examples 1-6 and Comparative Examples 1-3 were prepared, consisting mainly of the materials shown in Table 1. Specifically, powder materials prepared by mixing the compositions shown in Table 1 in predetermined proportions were first ground and mixed using a ball mill. In the following, sodium oxide (Na2O) was used as the alkali metal oxide. However, the content of each composition shown in Table 1 is the value calculated from the ceramic substrate after manufacturing, i.e., the sintered body. In Table 1, the unit of content, mass%, is expressed as wt%. Note that the values ​​shown in Tables 1 and 2 are the values ​​of each element in terms of oxide equivalent.

[0063] Next, polyvinyl butyral as an organic binder, xylene as a solvent, and dioctyl phthalate as a plasticizer were added to the pulverized and mixed powder material to form a slurry-like substance.

[0064] Next, a ceramic molded body was fabricated by forming the slurry-like material into a sheet using the doctor blade method.

[0065] Subsequently, the ceramic molded body was fired in an air atmosphere at a maximum temperature of 1565°C for 0.8 hours to obtain ceramic substrates according to Examples 1-6 and Comparative Examples 1-3. The heating rate from 1000°C to the maximum temperature was 85°C / min, and the heating time from the start to the maximum temperature was 70 minutes. The dimensions of this ceramic substrate were 0.32 mm in thickness, 39 mm in length, and 45 mm in width.

[0066] [Table 1]

[0067] Then, copper plates with an oxidized surface and a thickness of 0.3 mm were placed on the upper and lower surfaces of the ceramic substrates of the examples and comparative examples, and heated at atmospheric pressure under a nitrogen atmosphere at 1070°C for about 10 minutes. In this way, semiconductor device substrates according to Examples 1 to 6 and Comparative Examples 1 to 3 were obtained.

[0068] <2. Evaluation> The following evaluations were conducted.

[0069] (1) Evaluation method for grain boundary length For semiconductor device substrates in Examples 1-6 and Comparative Examples 1-3, the mass ratio of alkali metal oxide to the glassy second component was evaluated. Next, the bonding strength (bonding strength before DC (Direct Current) application) of the semiconductor device substrates was measured for Examples 1-6 and Comparative Examples 1-3. Subsequently, the bonding strength (bonding strength after DC application) was measured after applying DC 800V for 100 hours while heating each semiconductor device substrate at 150°C. Following this, the total interface distance (grain boundary length: X1) between adjacent Al2O3, ZrO2, and SiO2 was calculated by capturing the grain orientation distribution of Al2O3, ZrO2, and SiO2 using the EBSD (Electron Backscatter Diffraction) method. A grain boundary was defined as a case where the orientation difference between crystal grains was 5° or more. The measurement site was the central part of the cross-section of the ceramic substrate sandwiched between copper plates, and within the region observed at a magnification of 3,000x, a 30×30μm (900μm) area was measured. 2 The range of ) was defined as the EBSD observation area. The measurement results for Example 1 are shown in Figure 2.

[0070] (2) Method for measuring joint strength The joint strength was measured as follows: First, the rectangular copper plates being joined were peeled off from the end by a predetermined length along the longer side and bent at a 90° angle. Next, the end of the bent copper plate was clamped with a clip and pulled up vertically. The maximum value at that time was defined as the measured strength. That is, joint strength (kg / cm) = maximum lifting load (kg) / length of the shorter side of the rectangle (cm). Then, the ratio of the joint strength after DC application to the joint strength before DC application was calculated and defined as the joint strength ratio (%).

[0071] (3) Method for measuring bending strength The flexural strength of the ceramic substrates in Examples 1-6 and Comparative Examples 1-3 was measured by a three-point bending test in accordance with JIS R1601:2008.

[0072] (4) Consideration of joint strength and flexural strength The results are shown in Table 2. Examples 1-6 showed that the rate of decrease in bonding strength was less than 1.0% before and after DC application, indicating that a high level of bonding strength was maintained. On the other hand, Comparative Examples 1-3 showed a decrease in bonding strength of approximately 20-50% before and after DC application. This is because, in Examples 1-6, the alkali metal oxide content relative to the oxide content of the second component of the glassy material... Conversion This phenomenon is thought to be due to the effective suppression of oxygen ion conduction because the mass ratio of the content is 1.0 or less.

[0073] Furthermore, Examples 1 to 6 are, In relation to the content of alkali metals in terms of oxides, Total content of silica, magnesia, and the second glassy component in terms of oxides. Quantity While the mass ratio was 25.0 or higher in Comparative Examples 1-3, it was all below 25.0. In particular, as shown in Comparative Examples 1-3, it was found that the smaller this value was, the lower the bonding strength ratio. Therefore, it is considered that the larger this value was, the more effectively oxygen ion conduction was suppressed.

[0074] In Example 1 and Comparative Example 3, despite having equivalent zirconia and yttria content, a significant difference in bonding strength occurred before and after DC application. Therefore, SEM images of the cross-section of the ceramic substrate were obtained and shown in Figures 3 and 4, respectively. Comparing Figures 3 and 4, YSZ (white areas indicated by B2 and C2 in the figures) showed scattered behavior, and no mechanism of communication at grain boundaries was confirmed, so it can be said that the difference was not due to the difference in YSZ distribution. Therefore, the significant difference in the degree of bonding strength degradation before and after DC application, despite the equivalent amount of YSZ added, is thought to be due to the mass ratio of alkali metal oxide equivalent to the oxide equivalent mass of the second component of the glassy material. In other words, in Example 1, bonding strength was maintained because this value was 1.0 or less. On the other hand, in Comparative Example 3, bonding strength decreased because this value was higher than 1.0.

[0075] Furthermore, Figure 5 shows the results of impedance measurements performed for Example 1 and Comparative Example 3. In Figure 5, for example, 1.0E+03 means 1 multiplied by 10 to the power of 3. The measurement method used was the AC impedance measurement method. A DC voltage of 98.4V was applied to the semiconductor device substrate, and then an AC voltage of 1Vrms was applied to measure the impedance. As a result, Example 1 showed a higher impedance in the lower frequency range from 1.0E-03 to 1.0E+01 (Hz) than Comparative Example 3, confirming improved insulation. This is thought to be because Example 1 has a higher calcium content than Comparative Example 3.

[0076] Examples 1-6 and Comparative Examples 1-3 all showed a flexural strength of 550 MPa or higher. A flexural strength of 550 MPa or higher makes a DBOC substrate usable in a variety of applications. In particular, Examples 3 and 6 have higher zirconia content and lower silica content compared to Examples 1, 2, 4, and 5, resulting in higher flexural strength. [Table 2]

[0077] (5) Considerations regarding grain boundary length The results are shown in Table 3. The above-mentioned X1, A, B, C, A / (B×C), joint strength ratio, and flexural strength were calculated. As shown in Examples 1-6, A / (B×C) is 7.1×10 -4 Within the following range, it was found that DC durability improved and the joint strength ratio was also excellent. On the other hand, in Comparative Examples 1 to 3, the above calculated value (A / (B×C)) was all 7.1×10 -4 The size was larger, and the joint strength ratio was lower than that of Examples 1-6. [Table 3] [Explanation of Symbols]

[0078] 2… Circuit boards for semiconductor equipment 3…Ceramic substrate 4,4'...Copper plate

Claims

1. Al and, Zr and, Y and, Glassy and, It contains, The glassy material is The first component comprises Si, alkali metals (at least Na among Na, K, and Li), and O as elements. The second component includes at least one element selected from Ca, Sr, and Ba. Al of Al 2 O 3 The converted content is 84.56% by mass or more and 90% by mass or less. Zr's ZrO 2 The converted content is 9.10% by mass or more and 14% by mass or less. Y of Y 2 O 3 The converted content is 0.3% by mass or more and 0.73% by mass or less. Si's SiO 2 The converted content is 0.1% by mass or more and 1.16% by mass or less. The sodium content, calculated as Na₂O, is 0.02% by mass or more and 0.05% by mass or less. The mass concentration (mass%) in terms of oxide of the alkali metal that is the first vitreous component described above is defined as Al 2 O 3 , ZrO 2 , SiO 2 the value obtained by dividing by the total interface distance (grain boundary length) (μm) where they are adjacent to each other is defined as A (mass% / μm), The first component of the glassy material is Si SiO 2 Let B (mass%) be the converted mass concentration. When the total mass concentration of Ca, Sr, and Ba, which are the second components of the glassy material, in terms of oxides, is denoted as C (mass%), The value of A / (B×C) is 7.1×10 -4 (1 / (μm・mass%) or less, A ceramic substrate in which the mass ratio of the content of the alkali metal in oxide form to the content of the second glassy component in oxide form is 1.0 or less.

2. Zr's ZrO 2 The ceramic substrate according to claim 1, wherein the content, when converted, is 11% by mass or more.

3. A ceramic substrate according to claim 1 or 2, wherein the flexural strength is 550 MPa or more.

4. A ceramic substrate according to claim 1 or 2, wherein the flexural strength is 700 MPa or more.

5. A substrate for semiconductor devices for mounting electronic components, A ceramic substrate according to claim 1 or 2, A copper plate bonded to the ceramic substrate, A substrate for semiconductor devices, equipped with the following features.

Citation Information

Patent Citations

  • Ceramic sintered body, light-reflecting article, and package for storing light-emitting element

    JP2011241131A

  • Ceramic substrate and light-emitting device using the same

    JP2013230949A

  • Metal-ceramic composite substrate and semiconductor device

    JP2017224656A

  • Zirconia-alumina composite ceramic sintered body, its manufacturing method and applications

    JP2022515808A

  • Package for storing electronic component elements

    WO2012060341A1